2023
DOI: 10.1177/07334648231184950
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Predicts Injurious Falls Among Community-Dwelling Older Adults: Does Sex Matter?

Abstract: The association of poor nutritional status with falls-related injuries other than fractures is unclear. Although there are sex differences in poor nutritional status and the rate of falls-related injuries, whether the impacts of poor nutritional status on falls-related injuries differ by sex is unclear. We investigated whether baseline poor nutritional status predicted injurious falls, fall-related minor injuries, and fractures at 3-year follow-up and whether these relationships differed by sex among community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It is worth noting that malnutrition plays a crucial role in sarcopenia, significantly influencing its functionality, independence, and overall quality of life [15][16][17]. Extensive research has demonstrated that elderly individuals with inadequate nutrition face a greater risk of falling [18,19]. In addition, there is a relationship between nutrition and oral health.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that malnutrition plays a crucial role in sarcopenia, significantly influencing its functionality, independence, and overall quality of life [15][16][17]. Extensive research has demonstrated that elderly individuals with inadequate nutrition face a greater risk of falling [18,19]. In addition, there is a relationship between nutrition and oral health.…”
Section: Introductionmentioning
confidence: 99%